Brisk walking exercise as an effort to reduce blood glucose levels in diabetes mellitus - Mustika, I Wayan; Sudiantara, Ketut; Suardana, I Wayan; Gama, Ketut (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: Non-communicable diseases (NCDs) are a health problem that is currently the focus of global and national attention. One of the NCDs that can be found is Diabetes Mellitus (DM). The chronic metabolic disease called diabetes mellitus is caused by an insufficient amount of insulin produced by the pancreas or the body being unable to adequately use the insulin it produces. Diabetes cannot be cured, but blood sugar can be controlled to prevent complications. Physical exercise or exercise is the third and very important aspect in controlling diabetes. One physical exercise that can be done is brisk walking exercise for 30 minutes. Objective: To find out whether the implementation of brisk walking exercise can reduce blood glucose levels in diabetes mellitus sufferers in Wall Village, Tejakula District, Buleleng Regency in 2023. The type of research used is quasi-experimental with a nonequivalent control group design. The sampling technique used was non-probability sampling, namely purposive sampling, namely 30 respondents (15 intervention groups and 15 control groups). The Wilcoxon test results obtained ????-value 0.001 < alpha (0.05), which means there is a difference in blood glucose levels before and after brisk walking exercise in diabetes mellitus sufferers. Based on this research, it is recommended that brisk walking can be used as a non-pharmacological therapy to reduce blood glucose levels.